2022
DOI: 10.3389/fphar.2022.853568
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imaging Biomarkers to Guide Pharmacological Interventions Targeting Tumor Hypoxia

Abstract: Hypoxia is a common feature of solid tumors that contributes to angiogenesis, invasiveness, metastasis, altered metabolism and genomic instability. As hypoxia is a major actor in tumor progression and resistance to radiotherapy, chemotherapy and immunotherapy, multiple approaches have emerged to target tumor hypoxia. It includes among others pharmacological interventions designed to alleviate tumor hypoxia at the time of radiation therapy, prodrugs that are selectively activated in hypoxic cells or inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 617 publications
0
20
0
Order By: Relevance
“…Just as single-cell transcriptomics of tumor samples led to the identification of numerous clinical and molecular biomarkers [158], we anticipate that spatial variation in gene expression in the TME will also have high clinical relevance. For example, we showed that GASTON extracts gradients in gene expression that correlate with metabolism, the epithelial-mesenchymal transition (EMT) and other hallmarks of the TME which may translate to novel biomarkers for prognostics, treatment outcome prediction, and personalized medicine [28, 57, 44]. Additionally, GASTON introduces a new axis of tumor classification, in which tumors may be further characterized by the variation of distinct tumor processes across spatial gradients; for example, some tumors may have an increasing gradient of aerobic metabolism towards the tumor center (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Just as single-cell transcriptomics of tumor samples led to the identification of numerous clinical and molecular biomarkers [158], we anticipate that spatial variation in gene expression in the TME will also have high clinical relevance. For example, we showed that GASTON extracts gradients in gene expression that correlate with metabolism, the epithelial-mesenchymal transition (EMT) and other hallmarks of the TME which may translate to novel biomarkers for prognostics, treatment outcome prediction, and personalized medicine [28, 57, 44]. Additionally, GASTON introduces a new axis of tumor classification, in which tumors may be further characterized by the variation of distinct tumor processes across spatial gradients; for example, some tumors may have an increasing gradient of aerobic metabolism towards the tumor center (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since well-oxygenated, proliferating cancer cells can be targeted by chemo-, radio-and immunotherapies, our metabolic regimen is a natural candidate for combination with these therapies for synergistic therapeutic effects. Finally, this metabolic regimen may be similarly effective against a broad range of other FDG-PET-positive (glycolytic) tumors in other organs (10,18,71).…”
Section: Discussionmentioning
confidence: 99%
“…The BOLD parameters (T2*/R2* values) are related to the concentration of deoxyhemoglobin in local tissue, which can indirectly reflect the oxygen distribution state of the tissue. A high R2* value indicates a high local deoxyhemoglobin concentration, poor local oxygenation, and tissue in a hypoxic state (8,(10)(11)(12)21). High concentration oxygen can improve the dissociation of oxygen in capillary terminals and tissue spaces and cause the ratio of oxygenated-to-deoxyhemoglobin to increase.…”
Section: Discussionmentioning
confidence: 99%